Made for Sharing: George Cadbury, 'Industrial Betterment' and Salvation1. Issue 2 (December 2019) - Fincham, Andrew J.
Abstract : Both the business success and the philanthropic activities of Quaker magnate George Cadbury (1839–1922) are well known. However, historians (Quaker and otherwise) have largely neglected to consider the philanthropic activities centred on Bournville in the wider context of the contemporaneous movement for Industrial Betterment: given the similarity of activities, the question is prompted: 'what, if anything, was distinctly Quaker about George Cadbury's philanthropic activities?'. Using a contemporary evaluation of international Industrial Betterment, this article examines similarities between the settlements at Bournville and those created by industrialists who were not members of the Religious Society of Friends. Cadbury's actions are then considered in terms of Victorian philanthropy, the Social Gospel movement and the ethics of a contemporary Christian merchant. In conclusion, the article posits the existence of a motivational distinction, placing Cadbury's philanthropy within the distinctly Quaker tradition of 'building the Kingdom' on earth.